2011
DOI: 10.1038/onc.2011.404
|View full text |Cite
|
Sign up to set email alerts
|

Integrity of mTORC2 is dependent on the rictor Gly-934 site

Abstract: Growth factor signaling coupled to activation of the phosphatidylinositol-3-OH kinase (PI3K)/Akt pathway plays a crucial role in the regulation of cell proliferation and survival. The key regulatory kinase of Akt has been identified as mammalian target of rapamycin complex 2 (mTORC2), which functions as the PI3K-dependent Ser-473 kinase of Akt. This kinase complex is assembled by mTOR and its essential components rictor, Sin1 and mLST8. The recent genetic screening study in Caenorhabditis elegans has linked a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Rictor is an essential component of mTORC2 and is required for assembly and function of this complex (22)(23)(24)(25)(27)(28)(29), whereas mTORC2 phosphorylates serine 473 site in the hydrophobic motif of AKT (22)(23)(24)29). In initial studies, we examined the ability of IFN-α to induce AKT phosphorylation in MEFs with targeted disruption of the Rictor gene (30).…”
Section: Resultsmentioning
confidence: 99%
“…Rictor is an essential component of mTORC2 and is required for assembly and function of this complex (22)(23)(24)(25)(27)(28)(29), whereas mTORC2 phosphorylates serine 473 site in the hydrophobic motif of AKT (22)(23)(24)29). In initial studies, we examined the ability of IFN-α to induce AKT phosphorylation in MEFs with targeted disruption of the Rictor gene (30).…”
Section: Resultsmentioning
confidence: 99%
“…LAD2 cells were transfected with human myc-tagged rictor in a pRK5 plasmid kindly supplied by Dr. D. D. Sarbassov (39) as described (40). Briefly, 2 × 10 6 LAD2 cells were transfected using the Amaxa Nucleofector II system and then plated out in StemPro-34 medium supplemented with SCF and 100 ng/ml biotinylated human IgE for 6 h. This time point was chosen to achieve near maximal expression of rictor without discernible effects on cell morphology or viability.…”
Section: Methodsmentioning
confidence: 99%
“…It is conceivable that phosphorylation of the Ser-260 site on SIN1 by mTOR hinders a recognition site responsible for the disintegration of mTORC2 and lysosomal degradation of SIN1. It has been recently reported that a proper protein folding is critical in the assembly of mTORC2 and that a single amino acid substitution on rictor has precluded the assembly of mTORC2 (23). Because the endoplasmic reticulum has been identified as the main localization site of mTORC2 (27), this phosphorylation-dependent degradation pathway might be linked to proper protein folding monitoring by endoplasmic reticulum quality control that tags mTORC2 containing the non-phosphorylated form of SIN1 for disintegration and lysosomal degradation.…”
Section: Discussionmentioning
confidence: 99%
“…5A), the stable expression of SIN1 also indicates an important role of its Ser-260 site in controlling the integrity of mTORC2. Interestingly, regulation of the mTORC2 integrity by SIN1 phosphorylation on Ser-260 is independent of its binding partner rictor (23)(24)(25), because the SIN1 phosphomutants did not show any differences in binding to rictor. We also found that the abundance of mTORC2 induced by mimicking the mTOR-dependent phosphorylation of SIN1 carried out its functional activity not only by the elevated basal phosphorylation of Akt but also by a higher cell proliferation rate (Fig.…”
Section: Sin1 Phosphorylation On Ser-260mentioning
confidence: 99%